Simulation and experimental study of heat-moisture-solute transfer during drying process of porous media - Xu, Ying-ying; Niu, Jing-yi; Yuan, Yue-jin; Yuan, Yue-ding; Ma, Kai-kun (Drying technology, 2025)
Fruits and vegetables, being typical porous media, allow for the migration of nutrients (solutes) and the transport of moisture simultaneously during the drying process. To reveal the migration mechanism of heat-moisture-solute during the drying process of porous media, a comprehensive mathematical model was established that accounts for the coupled phenomena of heat and moisture transfer, along with solute migration. The model was simulated using COMSOL to provide insights into these complex interactions. Hot-air drying experiments were conducted using apple slices as the subject to validate the accuracy and reliability of the model. The simulation results and experimental results of temperature, moisture content, and sugar concentration were in good agreement. The findings demonstrate that as the drying process progresses, the interface between temperature, moisture gradients, and sugar concentration shifts from the outer layers toward the inner regions. We investigated the effects of hot air temperature, thickness, and porosity on the heat-moisture-solute transfer in porous media. The results provide support for accurately predicting the migration and transport mechanisms of solutes in porous media.